PENGGUNAAN SIYÄ€Q DALAM KITAB AL-TAFSá¿™R AL-á¸¤ADá¿™S KARYA MUHAMMAD IZZAT DARWAZAH - Anisatul Khoiriyah (AL ITQAN: Jurnal Studi Al-Qur'an, 2019)
Siyāq (context) has an important role in determining the meaning when interpreting the verses of the Qur'an. A sentence, expression, or language of text cannot be known and understood without looking at the context, either the language context or the context of the situation behind the text. This study uses a qualitative method with a siyāq (context) approach as an analysis tool for Muhammad Izzat Darwazah's interpretation in the book al-Tafsīr al-Ḥadīs. This is taken in order to find out how siyāq (context) is functioned, when and where it is used based on contextual theory, Dirāsah Mā fī al-Qur'ān and Dirāsah Mā Ḥaul al-Qur'ān theory. This study shows that in interpreting the verses of the Qur'an, Izzat Darwazah uses siyāq (context) to describe the meaning of the verses, determines the Makiyah and Madaniyah verses, determines some of the placement of  Madaniyah surahs order.